2006
DOI: 10.1007/s10517-006-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Myogenesis in hemopoietic tissue mesenchymal stem cell culture

Abstract: The myogenic differentiation capacity of prenatal mesenchymal stem cells from the main sites of hemopoiesis (bone marrow, thymus, liver, and spleen) was studied. Myogenesis was observed in all studied cell cultures except splenic mesenchymal stem cells. Differentiating cells from the thymus, bone marrow, and liver were positively stained for skeletal muscle markers (myogenin and MyoD). Autonomously contracting structures positively stained for cardiotroponin I and slow muscle myosin, were detected in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
3
1
Order By: Relevance
“…Such alteration in gene expression was not intrinsic to this particular study however, it was demonstrated that 5-Aza could not drive the myogenic differentiation of the tested OMLPPCs. This result differed to studies by Gornostaeva et al (2006) and Cheema, Yang, Mudera, Goldspink, & Brown (2003) where myogenesis was observed in prenatal-MSCs derived from the main sites of haemopoiesis (bone marrow, thymus, liver). Interesting however, this study failed to identify myogenic Positive immunostaining of OMLP-PC nuclei to human Lamin A/C (a) Hoechst nuclear stain (b) and overlaid images (c).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Such alteration in gene expression was not intrinsic to this particular study however, it was demonstrated that 5-Aza could not drive the myogenic differentiation of the tested OMLPPCs. This result differed to studies by Gornostaeva et al (2006) and Cheema, Yang, Mudera, Goldspink, & Brown (2003) where myogenesis was observed in prenatal-MSCs derived from the main sites of haemopoiesis (bone marrow, thymus, liver). Interesting however, this study failed to identify myogenic Positive immunostaining of OMLP-PC nuclei to human Lamin A/C (a) Hoechst nuclear stain (b) and overlaid images (c).…”
Section: Discussioncontrasting
confidence: 99%
“…The innate ability of embryologically distinct tissue types to differentiate to muscle has been attributed to a small percentage of pre-existing cells that already express myogenic genes such as Myf5, MYOD, Myogenin and Desmin (Gornostaeva, Rzhaninova, & Goldstein, 2006). However, all such reports to date have resulted in disappointingly small numbers of muscle differentiating cells.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs resemble mesenchymal stem cells (MSCs) in terms of their ability to differentiate into multiple lineages including adipocytes, myotubes, osteocytes, and cartilage under appropriate developmental cues (Gornostaeva et al, 2006). Given that increased numbers of adipocytes, a major underlying cause of obesity, are primarily derived from MSCs and/or ASCs (Bowers and Lane, 2008), we chose C3H10T1/2 MSCs as our cell culture model system for studying adipogenesis in large measure because MSCs efficiently recapitulate aspects of adipocyte differentiation and in vivo fat development.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, the fetal liver in different species has proved to contain precursor cells of skeletal muscles showing spontaneous fusion into myotubes in vitro [44][45][46]. These cells may enter the liver and other organs of the embryo when they migrate from the dermomyotome to populate areas where skeletal muscles are to be formed.…”
Section: Myoid Cellsmentioning
confidence: 99%